Effect of electronic governance in Auditing Quality Research applied at the Economic Organization - حمادي, صالح مهدي; ابراهيم, عمار غازي; عبد الكريم, نزار معن (Journal of Economics and Administrative Sciences, 2019)
The research paper aims to highlight the impact of electronic governance in improving the quality of auditing through accounting disclosure and how to make use out of it in resolving many of the problems by economic units in general and in particular the financial problems in particular. It focuses on the most important financial information of the loss of confidence and credibility in the financial information of the economic units, This study  has  been carried out through the use and application of many of the principles and rules contained in the electronic governance, The most important Which is the accounting disclosure, and hence the dimensions of accounting for electronic governance through the achievement of accounting control, developing the application of accounting and auditing standards, and the achieving accounting disclosure The research has reached several conclusions, the most important  of Which  is the failure to apply the principles and basics of E-governance in most economic units used that for electronic system. The most important recommendations for research is the need to apply the rules and principles of electronic governance in most economic.